2021
DOI: 10.1093/pubmed/fdab002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of isolating COVID-19 patients in a supervised community facility on transmission reduction among household members

Abstract: Background Isolation of COVID-19 patients has been universally implemented to control transmission of the outbreak. Hotels and other facilities have been adapted to help appropriate isolation be achieved. Our study tested the efficacy of isolating patients in a reconditioned hotel versus isolation in their domiciles to reduce infection transmission. Methods Observational cohort study based on a survey to COVID-19 patients bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…In our study, households who had adopted isolation or quarantine methods were more effective in preventing spread of the disease than households who did not implement complete isolation/quarantine measures from one another. When the case and his/her contacts are completely isolated or quarantined from the rest of the household [11,35], the household transmission was reduced. However, in our study, we found that reduced transmission could not be achieved due to the ineffective use of isolation and quarantine measures, inconsistent application of masks, or because of the spread of infection before any of these measures were taken.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, households who had adopted isolation or quarantine methods were more effective in preventing spread of the disease than households who did not implement complete isolation/quarantine measures from one another. When the case and his/her contacts are completely isolated or quarantined from the rest of the household [11,35], the household transmission was reduced. However, in our study, we found that reduced transmission could not be achieved due to the ineffective use of isolation and quarantine measures, inconsistent application of masks, or because of the spread of infection before any of these measures were taken.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, state-managed isolation facilities must also be established, instead of turning private homes into quarantine facilities, since management is more effective in these facilities. 42 Finally, the state must also consider the “cautious and gradual” reopening of schools 43 , 44 in order to give its citizens, at least, a semblance of normalcy.…”
Section: Managementmentioning
confidence: 99%
“…Therefore, the greater the number of people and time of permanence in the same space, the greater the statistical possibility of contagion. Therefore, the probability of infection increases by up to 30% among close household members, (López et al 2021 ). Although close contact between cohabitants is the main cause of contagion, this may also occur between different dwellings, especially through vertical building drainage stacks.…”
Section: Introductionmentioning
confidence: 99%
“…Contagion events have been documented by both the chimney effectinduced airflow in building drainage systems, especially in high-rise housing (Wang et al 2022), and through faecal aerosol transmission from toilets and washbasins (Kang et al 2020). This is why some studies have analysed the impact of the isolation of COVID-19 patients in community-supervised facilities, which may protect their household members from transmission of the disease (López et al 2021). Despite these, contagion of susceptible occupants from hotel-isolated patients can still occur through shared air from corridors, HVAC systems, and drainage stacks (Gu et al 2022;Hoefer et al 2020;Leong et al 2021).…”
Section: Introductionmentioning
confidence: 99%